2016
DOI: 10.1007/s00330-016-4413-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the coracoclavicular ligaments in the acute phase of an acromioclavicular disjonction: Comparison of radiographic, ultrasound and MRI findings

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. Comparison of radiographic, ultrasound and MRI findings. European Radiology, Any correspondence concerning this service should be sent to the repository administrator: staff-oatao@listes-diff.inp-toulouse.fr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Additionally, a provocative test was performed -the distance from the anterior border of the acromial process to the anterior border of the acromial end of the clavicle on the side of the injury was measured during the Paxinos test. In the sagittal projection, we determined coracoclavicular (CC) distance -between the most superior border of the coracoid process and the inferior border of the clavicle on the injured side [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a provocative test was performed -the distance from the anterior border of the acromial process to the anterior border of the acromial end of the clavicle on the side of the injury was measured during the Paxinos test. In the sagittal projection, we determined coracoclavicular (CC) distance -between the most superior border of the coracoid process and the inferior border of the clavicle on the injured side [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…Two studies demonstrated the diagnostic value of US in comparison to X-ray imaging 214 215 . Direct visualization of the coraco-clavicular ligament is almost as reliable with US as with the “gold standard” MRI 216 .…”
Section: Extraarticular Anatomical Structuresmentioning
confidence: 99%
“…US is signi cantly less expensive than computed tomography (CT) and magnetic resonance imaging (MRI). Therefore, US is most useful for determine the presence of various diseases and conditions, such as in ammation, rupture, and subluxation of the shoulder, arm, and hand [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…For basic training in US, medical students as well as medical residents must learn sectional anatomy for US using atlases that compare US images to CT, MRI, and schematic diagrams [3][4][5][6]. However, not all of the educational materials were su cient for learning the anatomy by US.…”
Section: Introductionmentioning
confidence: 99%